2021
DOI: 10.3952/physics.v61i1.4408
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency calibration of high-purity germanium detector using Monte Carlo simulations including coincidence-summing corrections: volume source case

Abstract: The gamma-ray spectrometry by the instrumentality of Ge detectors is used for the detection of low activity environmental samples of different geometry (soil samples, air filters with aerosols, milk powder, etc.). Such measurements require separate calibration of the detector. The high purity germanium (HPGe) gamma-ray spectrometer of GC2520 series was used for experiments. For the efficiency calibration, three cylindrical containers filled with different 60Co water solution levels were used, and the gamma-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…(1.0, 1.0) (0.9, 0.9) (0.8, 0.8) (0.7, 0.7) (0.6, 0.6) (0.5, 0.5) (0.4, 0.4) (0.3, 0.3) (0.2, 0.2) (0.1, 0.1) (0, 0) [8,14]. Previous studies on the same detector type have reported similar results to the results in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1.0, 1.0) (0.9, 0.9) (0.8, 0.8) (0.7, 0.7) (0.6, 0.6) (0.5, 0.5) (0.4, 0.4) (0.3, 0.3) (0.2, 0.2) (0.1, 0.1) (0, 0) [8,14]. Previous studies on the same detector type have reported similar results to the results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To measure the radioactivity of radionuclides accurately, the full-energypeak (FEP) efficiency of the detector must be calibrated, considering various geometric characteristics such as the size, shape, and composition of each sample [7]. In general, fulfill the 5% to 10% criteria according to the filling height of the cobalt-60 (60Co) volume source [8]. Aviv and Elia [10] used GEANT4 and FLUKA to correct the FEP difference of a broad-energy HPGe detector within 5% of the experimental value for point-like, filter paper, and water beaker-type sources.…”
Section: Introductionmentioning
confidence: 99%